The politics of truth : inside the lies that led to war and betrayed my wife's CIA identity : a diplomat's memoir - Wilson, Joseph C. (Joseph Charles), 1949-2019 (Carroll & Graf Publishers, 2004)
Wilson recounts his career in the U.S. Foreign Service, his public challenge to President George W. Bush's claim that Iraqi president Saddam Hussein sought uranium from Africa, the subsequent disclosure of the CIA undercover status of his wife, and his allegations that the Bush administration fabricated and manipulated intelligence to bolster its case for the invasion of Iraq.